Investigating the Effectiveness of the Financial Narrative Therapy on the Financial Anxiety and Financial Wellbeing among the Female Nurses in the Educational Hospitals - Marziyeh Malekiha; Mahboobe Doostkami; Farshid Saeedinezhad; Naser Yoosef; Somayeh Akafian (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background and Aim: Researchers in the field of financial health have recently paid attention to thefinancial wellbeing of individuals and the factors affecting which. Accordingly, various interventions andtherapies have been developed so far to maintain and improve the financial health of individuals. The aim ofthis study was to investigate the effectiveness of financial narrative therapy on reducing the financial anxietyand increasing the financial self-efficacy of female nurses.Methods: This semi-experimental research is pre-test and post-test with the control group. The statisticalpopulation of the study consisted of all female nurses of educational hospitals in year 2019. A total of30 people were randomly selected and assigned in both experimental and control groups (each with 15members). In this research, Financial Anxiety Scale (FAS) and Financial Well-Fare Questionnaire (FWQ)were used to collect data. The financial narrative therapy was conducted in eight 90-minute sessions in theexperimental group. Data were analyzed using SPSS-v.21 software and Statistical analysis of covarianceanalysis (ANCOVA).Results: The findings showed a significant difference between the mean of the experimental and controlgroup in two variables of financial anxiety and financial wellbeing (P <0.01). Based on this, it can beconcluded that financial narrative therapy has been effective in reducing the financial anxiety and increasingthe financial self-efficacy of the female nurses.Conclusion: Given the prominence of role of financial issues as a part of life in the today’s constantlychanging world, and the emergence of multiple sources of stress, financial narrative therapy can be used asan intervention to improve the financial health of individuals.